2007
DOI: 10.1080/10683160500337592
|View full text |Cite
|
Sign up to set email alerts
|

Risk and need assessment in British probation: the contribution of LSI-R

Abstract: From 1996 until about 2000 the Canadian Level of Service Inventory Á Revised (LSI-R) was in use in a number of probation services in England and Wales, and it is still in use in the Jersey Probation and After-Care Service. This article reviews what has been learned about risk and need assessment in British probation through the use of LSI-R, drawing on data collected for a Home Office study and for evaluative research in Jersey. Particular areas of interest are accuracy, differences between male and female off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 16 publications
3
87
2
2
Order By: Relevance
“…In contrast, a number of studies with adult samples have found changes in risk total scores to predict reoffending (Beggs & Grace, 2011;Blanchard, 2013;Cohen, Lowenkamp, & VanBenschoten, 2016;de Vries Robbé et al, 2015;Hogan & Olver, 2016;Labrecque, Smith, Lovins, & Latessa, 2014;Lewis, Olver, & Wong, 2013;Michel et al, 2013;Olver, Christofferson, Grace, & Wong, 2014;Olver, Nicholaichuk, Kingston, & Wong, 2014;Olver et al, 2007;Raynor, 2007;Vose, Smith, & Cullen, 2013;Wilson, Desmarais, Nicholls, Hart, & Brink, 2013), particularly after other variables are controlled for in analyses (e.g., baseline scores; see Appendix 3,Supplemental Material). That said, a couple of studies have failed to find significant associations between change scores and reoffending (Hanson, Harris, Scott, & Helmus, 2007;Hanson, 2015;Goodman-Delahunty & O'Brien, 2014).…”
Section: Dynamic Change Hypothesis: Changes In Risk Will Predict Reofmentioning
confidence: 99%
“…In contrast, a number of studies with adult samples have found changes in risk total scores to predict reoffending (Beggs & Grace, 2011;Blanchard, 2013;Cohen, Lowenkamp, & VanBenschoten, 2016;de Vries Robbé et al, 2015;Hogan & Olver, 2016;Labrecque, Smith, Lovins, & Latessa, 2014;Lewis, Olver, & Wong, 2013;Michel et al, 2013;Olver, Christofferson, Grace, & Wong, 2014;Olver, Nicholaichuk, Kingston, & Wong, 2014;Olver et al, 2007;Raynor, 2007;Vose, Smith, & Cullen, 2013;Wilson, Desmarais, Nicholls, Hart, & Brink, 2013), particularly after other variables are controlled for in analyses (e.g., baseline scores; see Appendix 3,Supplemental Material). That said, a couple of studies have failed to find significant associations between change scores and reoffending (Hanson, Harris, Scott, & Helmus, 2007;Hanson, 2015;Goodman-Delahunty & O'Brien, 2014).…”
Section: Dynamic Change Hypothesis: Changes In Risk Will Predict Reofmentioning
confidence: 99%
“…However, few studies have examined whether risk assessment scores change over time nor whether such changes actually increase or decrease future offending (with almost no research on changes in risk assessment scores as the result of targeted intervention and subsequent reoffending). The majority of notable exceptions have examined changes in adult probationers using the Level of Service Inventory-Revised (LSI-R; Raynor, 2007;Schlager & Pacheco, 2011;Vose et al, 2009). Raynor (2007), using the LSI-R, examined changes in the composite score and subsequent official offending in a sample of 360 adult probationers.…”
Section: Risk Assessment Change Scoresmentioning
confidence: 99%
“…The majority of notable exceptions have examined changes in adult probationers using the Level of Service Inventory-Revised (LSI-R; Raynor, 2007;Schlager & Pacheco, 2011;Vose et al, 2009). Raynor (2007), using the LSI-R, examined changes in the composite score and subsequent official offending in a sample of 360 adult probationers. Those probationers with an increase in composite LSI-R score evidenced a higher likelihood of new offending in comparison to those who evidenced a decreased composite LSI-R score.…”
Section: Risk Assessment Change Scoresmentioning
confidence: 99%
“…That said, the problem for rehabilitation is not just systematic (if unintended) biases in terms of who gets selected for 'correction' of which sorts and who gets defined as 'incorrigible', but also a more technical problem of the extent to which rehabilitation's resources (principally assessment tools and interventions approaches) are sufficiently sensitive to, for example, gender differences and cultural diversity (on which see, for example, Raynor, 2007;Robinson and Crow, 2009: Ch. 6).…”
Section: Criticisms Of Rehabilitationmentioning
confidence: 99%
“…There is no space here to properly review the renaissance of rehabilitation in the 1980s and 1990s (see Raynor andRobinson, 2009, Robinson, 2008). However, leaving aside the better known story of the advancement of the evidence base, it is worth recalling that there was also, in the 1980s a brief flurry of writing about new normative or philosophical approaches to rehabilitation, including Rotman's (1990) work (see also Cullen and Gilbert, 1982).…”
Section: Criticisms Of Rehabilitationmentioning
confidence: 99%